Lipid-based nanocomposites for mRNA delivery: Current trends and future challenges - Sorkhabi, Matin (Journal of Composites and Compounds, 2024)
Lipid nanoparticles (LNPs) are critical for the efficient delivery and intracellular transport of mRNA. They have recently been recognized as essential components of COVID-19 mRNA vaccines. Recent vaccinations have demonstrated the significant of lipid-based nanocomposite in the positive and effective delivery of mRNA therapies. These nanocomposites boost mRNA's efficacy by improving stability, biological uptake, and targeted delivery. We examine how lipid-based mRNA delivery methods are still being developed.